Comparative Analysis of Azerbaijani E-Government Websites for Efficiency Improvement - Imanov, Emil (ADA University, 2023)
This Master Thesis analyzes the current status of e-government portals in Azerbaijan, specifically selected five modules of e-taxes.gov.az websites. The analysis is comparative, where there are selected 5 international highest-ranking e-tax portals according to the UN to compare the selected criteria. The analysis includes selection of performance metrics and collect data on response time and availability of services. In addition, it involves front-end analysis, accessibility, and back-end analysis. Some steps consist of using ready tools such as webpage response time checker and webpage stack extraction. The front-end analysis method is the python code, which collects HTML data from webpages to check for best practices. According to the analysis, front end of some modules needs to be modernized. To collect the availability and performance data webpage monitoring tool was used. The data proved, that the services are down during the peak times. The back end was checked to understand the stack used, such as programming languages, frameworks, libraries, servers, and security certificates. This had shown that each module was developed totally different, and there is not standardized approach to the development of the services. This creates challenges on cross services data sharing.
Keywords: Technology Standards in E-Government; Cross-Service Data Sharing; E-government -- Azerbaijan -- Evaluation.; Website performance -- E-government portals -- Azerbaijan.; Azerbaijan -- Digital government services.; IT and Engineering